2011
DOI: 10.1177/014556131109000319
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Pharyngoesophageal Reconstruction with Combined Local and Regional Flaps: A Case Report

Abstract: We describe an unusual technique for performing delayed pharyngoesophageal reconstruction following circumferential pharyngolaryngectomy. Th e patient was a 52-yearold man who underwent a circumferential pharyngolaryngectomy for the treatment of hypopharyngeal carcinoma. In view of the patient's poor clinical status, we opted to perform a pharyngostomy and an esophagostomy and to postpone pharyngoesophageal reconstruction for a more appropriate occasion. Aft er the patient's clinical condition had suffi cientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Recently microvascular free flaps are considered the gold standard method for reconstruction of major defects following head and neck cancer surgery [12]. In the era of microsurgical free flaps, pedicled flaps still hold their position for the reconstruction of oral cavity cancers [13]. Study conducted by Pancholi M et al have shown PMMC flap to be easy, done early and adds to the bulk of reconstructed tissue thereby maintaining the contour especially in full thickness cheek defects post hemimandibulectomy or maxillectomy where a radial forearm flap will leave a distinct hollow due to lack of bulk [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently microvascular free flaps are considered the gold standard method for reconstruction of major defects following head and neck cancer surgery [12]. In the era of microsurgical free flaps, pedicled flaps still hold their position for the reconstruction of oral cavity cancers [13]. Study conducted by Pancholi M et al have shown PMMC flap to be easy, done early and adds to the bulk of reconstructed tissue thereby maintaining the contour especially in full thickness cheek defects post hemimandibulectomy or maxillectomy where a radial forearm flap will leave a distinct hollow due to lack of bulk [14].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] However, recently microvascular free flaps are considered the gold standard method for reconstruction of major defects following head and neck cancer surgery. [ 8 ] In the era of microsurgical free flaps, pedicled flaps still hold their position for the reconstruction of oral cavity cancers,[ 9 ] especially we have found great advantage of using PMMC flap as it is easy, done early and adds to the bulk of reconstructed tissue thereby maintaining the contour especially in full thickness cheek defects posthemimandibulectomy or maxillectomy where a radial forearm flap will leave a distinct hollow due to lack of bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in microsurgical techniques, pedicled flaps are still an acceptable option for the reconstruction of complex defects of the head and neck, especially intraoral defects and those of the hypopharynx and skin [ 8 ]. Various types of treatment for the relapse of head and neck cancer have been studied and discussed, mainly emphasizing radical resection and immediate reconstruction.…”
Section: Discussionmentioning
confidence: 99%